Answer:
g = h(e-10)
Step-by-step explanation:
You can multiply the whole equation by h to get g by itself.
To solve problems like this you can either graph or solve mathematically. To do the ladder we need to solve for one variable at a time. So lets cancel one variable out.
Multiply equation 1 by 2
This will give 4x-2y=14
Now we can get rid of y by subtracting 2 from 1
This will give x=9
Plug back in to either equation, i will use equation 2
3(9)-2y=5 simplify
-2y=-22 solve
Y=11
We can round 5.65 up to 6 and 3.4 down to 3.
3 * 6 = 18
now let's see how close our estimate is to the real answer
5.65 * 3.4 = 19.21
Our answer was pretty close to the real answer!
Hope I helped!
~ Zoe
Well first do you parentheses and the multiply all of your exponets